SYNTHESIS AND PROPERTIES OF COMPOUNDS YBa2-xSrxCu3O7 AND YBa2-xCaxCu3O7: UDC 546.64.43.55 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2016)
Complex oxide compounds based on transition metals 3d-series and rare earth elements with perovskite structure play an important role in the development of modern functional materials with special magnetic, superconducting, electro properties. Among the high-temperature superconducting compounds most closely studied experimentally and theoretically can be considered a system of Y-Ba-Cu-O. Moreover, from a technological point of view yttrium superconductors are the most promising because of its performance. So now, one of the most important problems of modern inorganic chemistry is to search for and obtain new promising materials with different magnetic and electro, as well as improving the performance of existing substances. We synthesized the set of samples of YBa2-xSrxCu3O7 and YBa2-xCaxCu3O7 composition using the method of solid-state synthesis. The crystal lattice parameters and the superconducting transition temperature were calculated for synthesized compounds. We investigated the dependence of systems parameters and crystal lattice symmetry type on x substitution degree. It was determined that the samples obtained by the solid-state method are single-phased. It is shown that obtained compounds have orthorhombic syngony, space group Р4/mmm. It is shown that a decrease in the ionic radius of alkaline earth element and with increasing degree of substitution decreases's parameters a, b and c orthorhombic phase synthesized compounds. In addition, with decreasing ionic radius decrease the volume of the unit cell. Investigated that the transition temperature to the superconducting state decreases with decreasing ionic radius values for all compounds compared to unsubstituted Y123 and also decreases with increasing degree of substitution for each of the compounds.
Keywords: superconductivity, crystal lattice, solid-state synthesis, critical temperature